Population Structure, Genetic Variation, and Linkage Disequilibrium in Perennial Ryegrass Populations Divergently Selected for Freezing Tolerance - Kovi, Mallikarjuna Rao; Fjellheim, Siri; Sandve, Simen R.; Larsen, Arild; Rudi, Heidi; Asp, Torben; Kent, Matthew Peter; Rognli, Odd Arne (Frontiers in Plant Science, 2015)
Low temperature is one of the abiotic stresses seriously affecting the growth of perennial ryegrass (Lolium perenne L. Understanding the genetic control of freezing tolerance would aid in the development of cultivars of perennial ryegrass with improved adaptation to frost. A total number of 80 individuals (24 of High frost [HF]; 29 of Low frost [LF] and 27 of Unselected [US]) from the second generation of the two divergently selected populations and an unselected control population were genotyped using 278 genome-wide SNPs derived from Lolium perenne L. transcriptome sequence. Our studies showed that the HF and LF populations are very divergent after selection for freezing tolerance, whereas the HF and US populations are more similar. Linkage disequilibrium (LD) decay varied across the seven chromosomes and the conspicuous pattern of LD between the HF and LF population confirmed their divergence in freezing tolerance. Furthermore, two Fst outlier methods; finite island model (fdist) by LOSITAN and hierarchical structure model using ARLEQUIN detected six loci under directional selection. These outlier loci are most probably linked to genes involved in freezing tolerance, cold adaptation and abiotic stress and might be the potential marker resources for breeding perennial ryegrass cultivars with improved freezing tolerance.